2012
DOI: 10.1097/mao.0b013e318255dd59
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Clinical Profile and Referral Pattern Differences of Vestibular Schwannomas and Other Cerebellopontine Angle Tumors

Abstract: A longer diagnostic delay was associated with cases involving other types of CPA lesions versus cases of VS, and tumor size and volume did not affect the diagnostic delay of the former. Moreover, the only significant difference in clinical presentation for these 2 groups of intracranial tumor involved Wave V latency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…16 This finding was similar in the adult population, although at a significantly decreased frequency compared with the 55%-95% documented in adults. 19,20 Similar to the findings of Evans et al, approximately one-fourth of our patients with NF2 presented with hearing loss. 6 In comparison, we found that a much larger proportion of pediatric patients with nonsyndromic VSs (69%) presented with asymmetrical hearing loss.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…16 This finding was similar in the adult population, although at a significantly decreased frequency compared with the 55%-95% documented in adults. 19,20 Similar to the findings of Evans et al, approximately one-fourth of our patients with NF2 presented with hearing loss. 6 In comparison, we found that a much larger proportion of pediatric patients with nonsyndromic VSs (69%) presented with asymmetrical hearing loss.…”
Section: Discussionsupporting
confidence: 77%
“…21,22 Ragab et al demonstrated that VS-type lesions at diagnosis were significantly smaller than non-VS lesions, which was confirmed in our study. 20 Additionally, we found that the average size of VS was larger in nonsyndromic patients than in NF2-affected children. The smaller tumor size and lower prevalence of hearing loss at presentation among pediatric patients with NF2, as compared with those factors in children with sporadic VS, is primarily explained by the high number of asymptomatic patients in whom NF2 was diagnosed as a result of early screening.…”
Section: Discussionmentioning
confidence: 62%
“…[ 11 ] Case reports show that this variant, while rare, has appeared in various locations from the filum terminale to cervicomedullary junction as well as intracranially arising from locations in the parenchyma and intraventricularly. [ 4 6 9 14 15 ]…”
Section: Discussionmentioning
confidence: 99%